Tendon derived magnetic hydrogel for bioprinting - Altheman, Vittoria Guerra [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Tendon injuries represent a significant portion of musculoskeletal disorders, with high morbidity and limited regenerative capacity. Tissue engineering strategies have shown promise by combining stem cells, biomaterials, and biophysical stimuli to promote functional tendon regeneration. This study aimed to develop a magnetically responsive hydrogel derived from the extracellular matrix (ECM) of porcine tendon for use as a bioink in 3D bioprinting and to evaluate its biocompatibility and potential for inducing tenogenic differentiation of mesenchymal stem cells derived from human adipose tissue (hASCs). The hypothesis was that the magnetic functionalization of the ECM would allow the application of remote magnetomechanical stimuli capable of modulating cellular mechanotransduction pathways, promoting cell alignment and increasing the deposition of tenogenic extracellular matrix compared to non-magnetically stimulated systems. To this end, pig tendons were subjected to an optimized decellularization protocol, followed by lyophilization and grinding. The resulting powder was digested to obtain the hydrogel. Rheological characterization confirmed properties suitable for bioprinting. The incorporation of zinc-doped iron oxide magnetic nanoparticles (Zn₀.₂₈Fe₂.₇₂O₄) conferred magnetic responsiveness to the material. Three-dimensional constructs were bioprinted with decellularized ECM bioinks and hASCs, with or without magnetic nanoparticles, on a cellulose crystal support medium (CNC). After printing, the models were cultured for up to 21 days, with and without exposure to low-intensity external magnetic fields. The results demonstrated high cell viability and maintenance of metabolic activity throughout the culture period, confirming the biocompatibility of the hydrogel. The presence of nanoparticles and magnetic stimulation did not compromise cell survival and favored cell alignment, with a tendency towards increased deposition of collagen and non-collagenous proteins in the groups exposed to the magnetic field. These findings suggest that magnetomechanical stimulation can act as a modulator of mechanotransduction pathways involved in tenogenesis. It is concluded that the hydrogel derived from porcine tendon extracellular matrix presents physicochemical and biological properties suitable for application as a bioink in 3D bioprinting. The magnetic hydrogel proved to be biologically active and mechanically stimulable, with potential as a functional model for the study of tenogenesis and future translational use.

Lesões tendíneas representam uma parcela significativa das afecções musculoesqueléticas, com alta morbidade e limitada capacidade regenerativa. Estratégias de engenharia tecidual têm se mostrado promissoras ao combinar células-tronco, biomateriais e estímulos biofísicos para promover a regeneração funcional do tendão. O presente trabalho teve como objetivo desenvolver um hidrogel magneticamente responsivo derivado da matriz extracelular (MEC) de tendão suíno para uso como biotinta em bioimpressão 3D e avaliar sua biocompatibilidade e potencial de indução da diferenciação tenogênica de células-tronco mesenquimais derivadas de tecido adiposo humano (hASCs). Partiu-se da hipótese de que a funcionalização magnética da MEC permitiria a aplicação de estímulos magnetomecânicos remotos capazes de modular vias de mecanotransdução celular, promovendo alinhamento celular e aumentando a deposição de matriz extracelular tenogênica em comparação a sistemas não magneticamente estimulados. Para isso, tendões suínos foram submetidos a um protocolo otimizado de descelularização, seguido de liofilização e moagem. O pó obtido foi digerido para obtenção do hidrogel. A caracterização reológica confirmou propriedades adequadas à bioimpressão. A incorporação de nanopartículas magnéticas de óxido de ferro dopadas com zinco (Zn₀.₂₈Fe₂.₇₂O₄) conferiu responsividade magnética ao material. Constructos tridimensionais foram bioimpressos com biotintas de MEC descelularizada e hASCs, com ou sem nanopartículas magnéticas, em meio de suporte de cristais de celulose (CNC). Após impressão, os modelos foram cultivados por até 21 dias, com e sem exposição a campos magnéticos externos de baixa intensidade. Os resultados demonstraram alta viabilidade celular e manutenção da atividade metabólica durante todo o período de cultivo, confirmando a biocompatibilidade do hidrogel. A presença das nanopartículas e o estímulo magnético não comprometeram a sobrevivência das células e favoreceram o alinhamento celular, com tendência ao aumento da deposição de colágeno e proteínas não colagênicas nos grupos expostos ao campo magnético. Esses achados sugerem que a estimulação magnetomecânica pode atuar como um modulador de vias de mecanotransdução envolvidas na tenogênese. Conclui-se que o hidrogel derivado da matriz extracelular de tendão suíno apresenta propriedades físico-químicas e biológicas adequadas para aplicação como biotinta em bioimpressão 3D. O hidrogel magnético mostrou-se biologicamente ativo e mecanicamente estimulável, com potencial como modelo funcional para estudo de tenogênese e futuro uso translacional.
Hidrogel magnético derivado de tendão para bioimpressão
Keywords: Extracellular matrix; Stem cell; Tenogenesis; 3D printing; Biomaterial